Local Government Unit (LGU) and Academe Partnership for Responsive e-Disaster Systems - Maria Victoria Pineda (Jurnal Sains & Teknologi Lingkungan, 2012)
Many developing countries have ventured to disaster management programs in the desire to minimize if not, eradicate disaster vulnerabilities and improve the coping skills of the people. Many ICT solutions have been developed and unfortunately, many of these are just one-time big-time solutions. Usability, transparency, costs of the systems and sustainability had become some of the issues. It is in this light that a working model of partnership between the academe and the local government unit (LGU) as a community is shaped. The academe takes the initiative in this endeavor. The tie-up is intended to support the LGU to become more responsive in managing its resources and addressing the needs of its constituents.The paper imparts the experience of the academe’s ICT project incubation for a community and further leads to a meaningful cooperation with the LGU. The ICT project developed is a flood prediction and mapping system for the province of Bulacan in the Luzon island of the Philippines.